Press "ONE" for English : Language Policy, Public Opinion, and American Identity - Schildkraut, Deborah J., 1973- (Book collections on Project MUSE., 2005)
"Using focus groups and survey data, Schildkraut develops a model of public conceptions of what it means to be American and demonstrates the complex ways in which people draw on these conceptions when forming and explaining their views. In so doing she illustrates how focus group methodology can help yield vital new insights into opinion formation."--Jacket